2010
DOI: 10.1017/cbo9780511845604
|View full text |Cite
|
Sign up to set email alerts
|

A Reference Grammar of Spanish

Abstract: A Reference Grammar of Spanish is a comprehensive handbook on the structure of the Spanish language. Keeping technical terminology to a minimum, it provides a detailed yet clear point of reference on all the intricacies of Spanish grammar, covering word order, parts of speech, verb use, syntax, gender, number, alphabet, and pronunciation. Accompanied by a wealth of carefully chosen examples, it looks at Spanish in Iberia, the USA, Mexico, and Argentina, and demonstrates the differences between these varieties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…To illustrate, the Official State Gazette of the Spanish government (N o 178 July 2011) explicitly states that students between the ages of 6 and 12 should learn to distinguish between and to be able to produce language of different degrees of formality. Moreover, Batchelor and San José (2010) dedicate the first chapter of their reference grammar of Spanish to register variation and how register variation affects Spanish grammar. As a consequence, we may safely assume that if the Spanish speakers in the NCSE have difficulties adapting their register in English, these are linguistic rather than cultural difficulties.…”
mentioning
confidence: 99%
“…To illustrate, the Official State Gazette of the Spanish government (N o 178 July 2011) explicitly states that students between the ages of 6 and 12 should learn to distinguish between and to be able to produce language of different degrees of formality. Moreover, Batchelor and San José (2010) dedicate the first chapter of their reference grammar of Spanish to register variation and how register variation affects Spanish grammar. As a consequence, we may safely assume that if the Spanish speakers in the NCSE have difficulties adapting their register in English, these are linguistic rather than cultural difficulties.…”
mentioning
confidence: 99%
“…The vast, still growing literature on this topic has made clear that the factors that account for null and overt pronominal subjects are far more complex than the traditional explanations that can be found in reference grammars. According to, for example, the grammars of Butt and Benjamin (2013), Batchelor and San José (2010) and Kattán-Ibarra and Howkins (2014), recurrent factors that determine the use of a subject pronoun are emphasis, disambiguation and contrast. While especially contrastive uses and disambiguation are uncommon in natural data (Posio 2013: 256), studies like that of Enríquez (1984), Davidson (1996), Lipski (2002), Aijón Oliva andSerrano (2010), Travis andTorres Cacoullos (2012) and several publications of Posio (2011Posio ( , 2013Posio ( , 2014 have shown that grammatical factors such as person, mode and tense, the semantic category of verb, semantic roles, pragmatic weight (a speech act reading), priming (perseveration), particular formulaic constructions, the discourse type, as well as regional variation can explain the choice for a null or an explicit subject pronoun.…”
Section: Creo Que or Yo Creo Quementioning
confidence: 99%
“…All grouped "nine in total" and with unique grammar-shapes. Although the adjectives and descriptive adjectives do not have gender in Spanish; they are subjected to follow the same patterns (gender and number) when they adhered to these grammar themes (article/noun) (Batchelor, José, & Ángel, 2010). The way with which these syntaxes components are treated referring to the use of gender (masculine/feminine) and the number (singular/plural) and the arrangement (words order) of nouns, articles and descriptive adjectives into the writing and speaking context of Spanish language communication makes more challenging the teaching and learning of these grammar themes in Spanish FL classes, essentially when working with 2L learners whose native-language does not apply the "gender/number/words-order" as Spanish does.…”
Section: Introductionmentioning
confidence: 99%